Knowledge and Attitude of Mental Illness Among General Public of Southern India - K Ganesh (Medsci Publications, 2011)
Background: Mental disorders are widely recognized as a major contributor to the global burden of disease worldwide. The aim of this study was to examine the knowledge and attitude about mental illness among general public. Method: This is a cross-sectional survey conducted from October 2008 to March 2009. A questionnaire was designed to assess knowledge, attitude, and practice regarding mental illness. Results: 100 subjects were selected conveniently, of which 33 % males and 67 % females, most of them in the age group above 30 years. Mean knowledge score of the subjects was 5.90 ± 1.22. Item wise awareness regarding mental illness were common mental disorders (60%), causes (35%), signs and symptoms of mental illness (60%), treatment (42%) and prognosis 30 % and most of them had negative attitude towards mental illness. High knowledge score has been associated with male and aged between 18-30 years. Conclusion: Knowledge of mental illness among the general public was quite poor and suggests the need for strong emphasis on public education to increase mental health literacy among general public to increase awareness and positive attitude of people towards mental illness.